Neutral lumbar spine sitting posture in pain-free subjects - O'Sullivan, K.; O'Dea, P.; Dankaerts, Wim; O'Sullivan, Peter; Clifford, A.; O'Sullivan, L. (Churchill Livingstone, 2010)
Sitting is a common aggravating factor in low back pain (LBP), and re-education of sitting posture is a common aspect of LBP management. However, there is debate regarding what is an optimal sitting posture. This pilot study had 2 aims; to investigate whether pain-free subjects can be reliably positioned in a neutral sitting posture (slight lumbar lordosis and relaxed thorax); and to compare perceptions of neutral sitting posture to habitual sitting posture (HSP). The lower lumbar spine HSP of seventeen pain-free subjects was initially recorded. Subjects then assumed their own subjectively perceived ideal posture (SPIP). Finally, 2 testers independently positioned the subjects into a tester perceived neutral posture (TPNP). The inter-tester reliability of positioning in TPNP was very good (intraclass correlation coefficient (ICC) = 0.91, mean difference = 3% of range of motion). A repeated measures ANOVA revealed that HSP was significantly more flexed than both SPIP and TPNP (p <0.05). There was no significant difference between SPIP and TPNP (p >0.05). HSP was more kyphotic than all other postures. This study suggests that pain-free subjects can be reliably positioned in a neutral lumbar sitting posture. Further investigation into the role of neutral sitting posture in LBP subjects is warranted.